Fabrication and evaluation of hydrogel film containing Centella asiatica for wound healing - Ahmed, Afnan Shihab (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Nowadays, one of the biggest challenge facing the health care providers is addressing the wounds. Thus a medicated hydrogel dressing which minimizes the time for healing and increases the patient compliance is important. Hydrogels are three-dimensional, water swollen structures. Development of hydrogel films as a wound-healing dressing is of great interest owing to their biological tissue like nature. The objectives of the study were to fractionate Centella asiatica and determine the asiaticoside-rich fraction, to formulate hydrogels using polyvinyl alcohol and polyethylene glycol and characterize the physico-chemical properties of the formulations and to evaluate the in vitro and the in vivo efficacy of the optimized C. asiatica hydrogel formulation. Polyvinyl alcohol/polyethylene glycol (PVA/PEG) hydrogels were successfully developed using freeze-thaw method. Response surface methodology by using Box-Behnken experimental design was employed to optimize the hydrogels. The hydrogels were characterized and optimized by gel fraction, swelling index, water vapour transmission rate and mechanical strength. The formulation with 8 % PVA, 5% PEG 400 and 5 consecutive freeze-thaw cycles was selected as the optimized formulation. The ethanolic extract of C. asiatica was fractionated into seven fractions and the asiaticoside-rich fraction (methanolic fraction) was selected to be incorporated into the optimized hydrogel formulation. The final formulation (CAEMF hydrogel) was subjected to further in vitro and in vivo studies. For the in vitro studies, the hydrogel formulation was characterized by its drug release, rheological properties, SEM, in vitro biocompatibility and microbial studies. While for the in vivo incisional wound healing studies, skin irritation, wound epithelisation, ultrasound measurements, hydroxyproline content and histopathological studies were conducted on New Zealand white Albino male rabbits. The optimized formulation showed a zero-order kinetics release with more than 90% drug release at 12 hours. The SEM studies shows that the PVA/PEG hydrogel films have compact surface with large number of pores. The rheological properties exhibited that the formulation has a viscoelastic behaviour. Cell culture studies confirmed the biocompatible nature of the optimized hydrogel formulation. For the microbial limit tests, the optimized hydrogel showed no microbial growth. The accelerated stability data showed that the CAEMF hydrogel was stable upon the 6 months storage period. From the in vivo studies, no irritation reported from the hydrogels on rabbits' skin. Healing in CAEMF hydrogel was more than 15% faster than commercial cream and more than 40% faster than untreated wounds. The hydroxyproline content shows a slightly higher hydroxyproline level in CAEMF hydrogel and Madicassol cream as compared to blank hydrogel and no treatment. The ultrasound images implies all skin wounds were intact. Skin healing was seen in all wounds marked by formation of a thick epithelial layer, keratin, and moderate formation of granulation tissues, fibroblasts and collagen with no fibrinoid necrosis detected. These results demonstrated the possible applicability of optimized CAEMF hydrogel as a wound dressing due to its sweallabilty, elasticity, safety and efficacy in accelerating the wound healing in an early stage of treatment. Hence, the CAEMF PVA/PEG hydrogel prepared by freeze-thaw method could be considered as a promising new wound dressing formulation.